Risking Net Zero; Perspectives from Geographic Political Economy on the UK’s ‘De-risking’ Climate Finance regime - MATTHEW KELLY (2024)
This thesis sets out to explore some of the key dimensions in the institutionalisation of the UK’s De-risking climate finance regime- a regime that seeks to embed the consideration of climate risk in financial markets, and as such, enable the marketization of UK and international climate finance. The institutionalisation of this regime is not driven solely by climate-related financial policy, but also by wider climate policy and related concerns such as UK industrial strategy and devolved climategovernance. As such some of the drivers that have greatest relevance to the institutionalisation of the UK De-risking regime are the outcomes of broader political organisation, economic structure and performance. From the diverse dimensions of institutionalisation one underlying question emerges: can the incorporation of climate risks in investment decision-making provide anadequate incentive to drive the scale and pace of investment required to deliver Net Zero in the UK and internationally? This thesis is structured over five chapters. Chapter one synthesizes a review of literature, examining the history and outlining a conceptual framework for the UK De-risking regime. Chapter two outlines the methodology for the thesis, and the Geographic Political Economy approach. Chapter three is the first of three empirical chapters and outlines an institutional systems map of UK Climate Finance. This provides key context for subsequentchapters and illustrates the scope and complexity of the task set by the UK De-risking regime to embed the consideration of climate risk in financial markets. Chapter four explores how Geo-FinTech can integrate climate-related financial disclosures to identify and measure climate related financial risk, its capabilities, institutionalisation, limitations and implications for the De-risking regime and UK industrial strategy. Chapter five explores how devolved climate governance in Wales drives or inhibits the institutionalisation of the UK De-risking regime and implications for path dependencies of Climate Finance in Wales. Chapter six outlines the conclusions of this research anddraws out its implications for UK climate related financial policy as well as mapping out some areas for further research. In particular, I outline the need to consider more direct forms of structured public investment, that enable devolved governance to deliver the scale and pace of investment required for UK Net Zero.